Navigating Sri Lankan identity in a state of crisis : the role of the creative imaginary - Jeslyn Sharnita Amarasekera; Shanthini Pillai (Penerbit Universiti Kebangsaan Malaysia, 2022)
Sri Lanka is often thought of as a nation that has been in a constant state of crisis since the start of its civil war in 1983. However, with the passing of time and various government efforts, there have been attempts to heal the tears in the social fabric. Some of these attempts can be seen in the creation of the National Policy on Reconciliation and Co-Existence, of 2017 as well as the establishment of the Office of National Unity and Reconciliation. While these have clear missions towards an inclusive Sri Lankan society, the reality of the state of affairs in Sri Lanka has revealed that there is an ongoing racial and cultural divide that continues to prevail within the nation. This paper intends to delve into how Sri Lankan transnational authors offer an alternative narrative towards achieving national reconciliation as their works of fiction navigate the various trajectories of Sri Lankan identity in an age of crisis. The discussion will focus specifically on Nayomi Munaweera’s Island of a Thousand Mirrors and Ameena Hussein’s The Moon in the Water to uncover how their creative imaginary reveals the unraveling of the threads of cultural and religious interactions between various Sri Lankan characters of different ethnic backgrounds. The paper reveals that even though these two works of fiction address past violence and conflict, they ultimately show the strong possibilities of attaining the envisioned shared future as promised in the various government designed narratives.